Student Voice and Participation in Intercultural Education - Ana Paula Caetano; Isabel Pimenta Freire; Elsa Biscaia Machado (Springer, 2020)
This paper presents a multi-case study in the field of intercultural education and it refers to a project named "Voice of children and young people in the development of intercultural education". The cases are critical action-research projects developed with three groups of middle and high school students. They participated in dialogic processes and shared leadership with their teachers. They co-designed projects, debated and became aware of critical issues related to cultural diversity in their educational communities. The purpose of the research is to analyze participatory processes and associated changes in relation to intercultural education and students' voice frameworks. Personal changes of the students, such as self-awareness and attention to others and to relationships, and group changes such as cohesion, were underlined, as well as changes extended to other actors -teachers, other students, staff, tutors, and other members of the community- creating collaborative relationships, solidarity, and mutual recognition. There were visible changes during the most active period in which projects were held, but sometimes impacts still endured and deepened afterwards. This stresses the relevance of youngsters' participatory projects engaged in intercultural processes and change.